Cellular Activation, Differentiation, and Proliferation Influence the Dynamics of Genetically Intact Proviruses Over Time. (26th May 2021) - Horsburgh, Bethany A; Hiener, Bonnie; Fisher, Katie; Lee, Eunok; Morgan, Hannah; Eden, John-Sebastian; von Stockenstrom, Susanne; Odevall, Lina; Milush, Jeffrey M; Hoh, Rebecca; Fromentin, Rémi; Chomont, Nicolas; et al.
Abstract: Human immunodeficiency virus (HIV) persists in cells despite antiretroviral therapy; however, the influence of cellular mechanisms such as activation, differentiation, and proliferation upon the distribution of proviruses over time is unclear. To address this, we used full-length sequencing to examine proviruses within memory CD4 + T-cell subsets longitudinally in 8 participants. Over time, the odds of identifying a provirus increased in effector and decreased in transitional memory cells. In all subsets, more activated (HLA-DR–expressing) cells contained a higher frequency of intact provirus, as did more differentiated cells such as transitional and effector memory subsets. The proportion of genetically identical proviruses increased over time, indicating that cellular proliferation was maintaining the persistent reservoir; however, the number of genetically identical proviral clusters in each subset was stable. As such, key biological processes of activation, differentiation, and proliferation influence the dynamics of the HIV reservoir and must be considered during the development of any immune intervention. Abstract : The longitudinal analysis of full-length proviruses within memory CD4 + T-cell subsets demonstrates that the biological processes of activation, differentiation, and proliferation influence the dynamics of the HIV reservoir, and must be considered during the development of any immune intervention.